Benedictus es domine, the Ambrosian Canticle of the Three Children in the Fiery Furnace. Issue 2 (October 2021) - BAILEY, TERENCE
Abstract: The hymn of Shadrach, Meshach and Abednego from the Book of Daniel was sung in Milan as the first canticle of Ambrosian Matins on all Sundays and festivals. The Benedictus es domine had a special importance in the Milanese liturgy: it was not only the first lection of the day, but was also seen as providing a common theme unifying the morning office. Those who study Milanese chant will be interested in the details of its performance, but the hope is that even those who do not usually take note of things Ambrosian will welcome an illustration of the extraordinary complexity that characterises the Rite in its final stage.